2018
DOI: 10.1155/2018/2976985
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization, Microbiological Quality and Safety, and Pharmacological Potential of Hancornia speciosa Gomes

Abstract: Hancornia speciosa Gomes is a fruit tree, commonly known as the mangaba tree, which is widespread throughout Brazil. The leaves of this plant are used in traditional medicine for medicinal purposes. Thus, the objective of this study was to perform a physicochemical characterization, identify the lipophilic antioxidants and fatty acids, and determine the microbiological quality and safety of H. speciosa leaves. In addition, the antioxidant, antimutagenic, and inhibitory activities of the ethanolic extract of H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 100 publications
2
14
0
Order By: Relevance
“…Many of these contaminants in non-sterile pharmaceuticals can alter their therapeutic properties and damage health (Ratajczak et al, 2015). The presence of the pathogenic microorganism Bacillus cereus exclusively in the S. terebinthifolius root powder and the absence of microbial growth in the extracts of all plant parts may indicate the microbiological safety of these plant materials, characterizing them as high-quality natural products (Santos et al, 2018). Furthermore, the absence of toxicity signs in the acute toxicity test supports the pharmacological potential of S. terebinthifolius.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these contaminants in non-sterile pharmaceuticals can alter their therapeutic properties and damage health (Ratajczak et al, 2015). The presence of the pathogenic microorganism Bacillus cereus exclusively in the S. terebinthifolius root powder and the absence of microbial growth in the extracts of all plant parts may indicate the microbiological safety of these plant materials, characterizing them as high-quality natural products (Santos et al, 2018). Furthermore, the absence of toxicity signs in the acute toxicity test supports the pharmacological potential of S. terebinthifolius.…”
Section: Discussionmentioning
confidence: 99%
“…The dichloromethane fraction is also composed of esters of lupeol and/or α/β-amirin. Through gas chromatography, Santos et al (2018) identified 22 lipophilic compounds from H. speciosa leaf extract, where the α-linolenic acid was the predominant fatty acid identified, followed by palmitic and linoleic acids. The sample had a higher percentage of polyunsaturated fatty acids (PUFAs; 48.82%), followed by saturated fatty acids (SFAs; 39.19%) and monounsaturated fatty acids (MUFAs; 11.86%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the biological activities of H. speciosa leaves, demonstrating antibacterial (Barbosa et al, 2019), anti-diabetic (Pereira et al, 2015), antihypertensive (Silva et al, 2011, 2016; Moreira et al, 2020), antioxidant, antimicrobial, and cytotoxic effects (Santos et al, 2016). Santos et al (2018) also identified that the plant leaf extract has antioxidant, antimutagenic, anti-inflammatory, anti-Alzheimer's disease, anti-Parkinson's disease, antiobesity, and antihyperglycemic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts prepared from the leaves of S. velutina in an ethanol solvent were found to be very potent inhibitors of radical scavenging activity by the DPPH (2,2′-diphenyl-1-picrylhydrazyl) method, and the concentration necessary for the 50% inhibition (IC 50 ) of DPPH of these extracts was lower than that of the commercial antioxidant butylated hydroxytoluene (BHT) (6.3 ± 1.3 versus 21.3 ± 1.2 μ g/mL). Similarly, Dos Santos et al [46] evaluated the antioxidant capacity of a leaf extract of Hancornia speciosa in an ethanolic solvent and also observed a potential activity by the DPPH method and improved IC 50 values in relation to BHT (9.4 ± 0.8 versus 66.1 ± 23.6 μ g/mL).…”
Section: Redox Balance Potentialmentioning
confidence: 99%
“…Dos Santos et al [46] evaluated the cell death profile of an extract from H. speciosa in an acute myeloid leukaemia cell line, Kasumi-1. The extract from H. speciosa promoted caspase-independent apoptosis because the pancaspase inhibitor did not inhibit the cytotoxic activity of these extracts.…”
Section: Cell Death Profile Induced By Plants From the Cerradomentioning
confidence: 99%